2021
DOI: 10.3758/s13421-020-01118-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences of domain knowledge on segmentation and memory

Abstract: Much research has shown that experts possess superior memory in their domain of expertise. This memory benefit has been proposed to be the result of various encoding mechanisms, such as chunking and differentiation. Another potential encoding mechanism that is associated with memory is event segmentation, which is the process by which people parse continuous information into meaningful, discrete units. Previous research has found evidence that segmentation, to some extent, is affected by top-down processing. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 66 publications
1
35
1
Order By: Relevance
“…It is also possible that knowledge can affect memory in other ways than by influencing eye movements. Some work has shown that knowledge can influence memory independently from how information is encoded (Newberry et al, 2021 ; Sargent et al, 2013 ). This possibility is surprising given all the work that assumes that knowledge affects memory by improving encoding (Anderson & Pichert, 1978 ; Reingold et al, 2001a , 2001b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that knowledge can affect memory in other ways than by influencing eye movements. Some work has shown that knowledge can influence memory independently from how information is encoded (Newberry et al, 2021 ; Sargent et al, 2013 ). This possibility is surprising given all the work that assumes that knowledge affects memory by improving encoding (Anderson & Pichert, 1978 ; Reingold et al, 2001a , 2001b ).…”
Section: Discussionmentioning
confidence: 99%
“…A third aspect is inter-individual agreement about where to place boundaries in an action sequence. In videos of figure skating routines and basketball games, experts agreed on more boundaries than novices, which could indicate the use of expert knowledge ( Levine et al, 2017 ; Newberry et al, 2021 ). However, in figure skating, experts and novices tended to place most boundaries at the goals of the actions or at the beginnings ( Levine et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the impact of sensorimotor impairment, also motor skill increase is reflected in action segmentation, as addressed by a few studies. Most of them involved closed-loop, mostly internally guided actions, i.e., dancing and figure skating ( Bläsing, 2014 ; Levine et al, 2017 ; Di Nota et al, 2020 ) and recently basketball ( Newberry and Bailey, 2019 ; Newberry et al, 2021 ). Different aspects were highlighted in these studies and some criteria were identified to possibly determine segmentation judgments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could also be greater for online data collection, a practice that is increasing, which offers little control over either the context in which data collection occurs or the hardware that is being used. Additionally, there may be individual and group differences that could influence how events themselves are processed and segmented, though these factors have as yet received little attention in the literature (for exceptions, see Bläsing, 2015;Kurby & Zacks, 2011;Levine et al, 2017;Newberry et al, 2021;Sargent et al, 2013;Swallow & Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%